Cystathionine beta-synthase mutations: effect of mutation topology on folding and activity - Kozich, Viktor; Sokolová, Jitka; Klatovská, Veronika; Krijt, Jakub; Janosík, Miroslav; Jelínek, Karel; Kraus, Jan P (Human mutation, 2010)
Misfolding of mutant enzymes may play an important role in the pathogenesis of cystathionine beta-synthase (CBS) deficiency. We examined properties of a series of 27 mutant variants, which together represent 70% of known alleles observed in patients with homocystinuria due to CBS deficiency. The median amount of SDS-soluble mutant CBS polypeptides in the pellet after centrifugation of bacterial extracts was increased by 50% compared to the wild type. Moreover, mutants formed on average only 12% of tetramers and their median activity reached only 3% of the wild-type enzyme. In contrast to the wild-type CBS about half of mutants were not activated by S-adenosylmethionine. Expression at 18 degrees C substantially increased the activity of five mutants in parallel with increasing the amounts of tetramers. We further analyzed the role of solvent accessibility of mutants as a determinant of their folding and activity. Buried mutations formed on average less tetramers and exhibited 23 times lower activity than the solvent exposed mutations. In summary, our results show that topology of mutations predicts in part the behavior of mutant CBS, and that misfolding may be an important and frequent pathogenic mechanism in CBS deficiency.
Keywords: mutace; cystathionin-beta-synthasa; Catalysis; Protein Structure, Tertiary; Escherichia coli; Blotting, Western; katalýza; Protein Structure, Quaternary; terciární struktura proteinů; lidé; Solubility; Cystathionine beta-Synthase; Mutation; rozpustnost; Cold Temperature; Protein Multimerization; Models, Molecular; western blotting; Mutant Proteins; molekulární modely; sbalování proteinů; katalytická doména; Protein Folding; Catalytic Domain; mutantní proteiny; kvarterní struktura proteinů; Homocystinuria; multimerizace proteinu; Enzyme Stability; nízká teplota; homocystinurie; stabilita enzymů; Humans